2021
DOI: 10.1039/d0ra10307a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of 5-ethoxymethylfurfural from biomass-derived 5-hydroxymethylfurfural over sulfonated organic polymer catalyst

Abstract: The sulfonic acid grafted porous organic nitrogen-containing polymer (PDVTA-SO3H) exhibited excellent catalytic activity in the synthesis of 5-ethoxymethylfurfural (EMF) from 5-hydroxymethylfurfural (HMF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Efficient conversion of biomass into bio-based platform compounds and biofuels is one of the most important technological challenges. 1,2 5-Hydroxymethylfurfural (HMF) is a vital biomass-transformed platform chemical for biomass and biofuel, 3,4 which can be further converted into various value-added derivatives such as 2,5-dimethylfuran (DMF), 5 5-diformylfuran (DFF), 5-ethoxymethylfurfural (EMF), 6 2,5-furandicarboxylic acid (FDCA) 7 and other furan chemicals. 8,9 It is important to emphasize that 5-ethoxymethylfurfural (EMF) has a high energy density of 8.7 kW h L À1 , which is equivalent to standard gasoline (8.8 kW h L À1 ) and diesel fuel (9.7 kW h L À1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Efficient conversion of biomass into bio-based platform compounds and biofuels is one of the most important technological challenges. 1,2 5-Hydroxymethylfurfural (HMF) is a vital biomass-transformed platform chemical for biomass and biofuel, 3,4 which can be further converted into various value-added derivatives such as 2,5-dimethylfuran (DMF), 5 5-diformylfuran (DFF), 5-ethoxymethylfurfural (EMF), 6 2,5-furandicarboxylic acid (FDCA) 7 and other furan chemicals. 8,9 It is important to emphasize that 5-ethoxymethylfurfural (EMF) has a high energy density of 8.7 kW h L À1 , which is equivalent to standard gasoline (8.8 kW h L À1 ) and diesel fuel (9.7 kW h L À1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, adjusting the dosage of DHA, AN, and BDSA could control the acid strength and density of D-SPC that could pick the yield of EMF (68.8%). Xiang et al [78] also assembled a sulfonic acid-based porous organic polymer (PDVTA-SO 3 H); they first synthesised PDVTA by mixing divinylbenzene (DVB) and triallylamine (TAA) by a solvothermal copolymerization method, and then, PDVTA-SO 3 H was prepared by the sulfonation process of PDVTA. ey used the Box-Behnken response surface method to adjust the reaction conditions and observed a 99.8% HMF conversion and 87.5% EMF yield at 110 °C within 30 min.…”
Section: So 3 H-based Catalystsmentioning
confidence: 99%
“… 1 According to the best knowledge of the authors, the studies of Ras et al 1 , 11 , 25 are the only openly available studies that focus specifically on this reaction with the aim of modeling the catalyst performance. Studies that focus on the synthesis of 5-EMF can be found, for example, in refs ( 23 , 24 ). This article focuses on ML and modeling rather than on the chemistry of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction studied in this work is the hydrogenation of 5-ethoxymethylfurfural (5-EMF), which is an important reaction related to the conversion of biomass into biofuels. ,, The desired product is 5-ethoxymethylfurfuryl alcohol, which is a potential additive for diesel fuel . 5-EMF can be easily obtained via acid-catalyzed dehydration of C6 sugars with ethanol as a solvent .…”
Section: Introductionmentioning
confidence: 99%